Accelerated healing of a diabetic foot ulcer using autologous stromal vascular fraction suspended in platelet-rich plasma. (1st May 2018) - Didangelos, Triantafyllos; Koliakos, George; Kouzi, Kokkona; Arsos, George; Kotzampassi, Katerina; Tziomalos, Konstantinos; Karamanos, Dimitrios; Hatzitolios, Apostolos I
We describe the case of a Type I diabetic patient with a refractory foot ulcer that remained unhealed for 2 years despite conventional therapy. Autologous adipose-derived stromal vascular fraction suspended in autologous platelet-rich plasma was applied to the wound, which completely healed within 1 month. The wound remained closed with no complications for a 2-year follow-up. Reporting of this and similar cases may lead to larger clinical trials that will prove the efficacy of this therapy that may offer accelerated healing and lessen the financial burden of more expensive therapeutic modalities.